Thirteen Days to Midnight - Carman, Patrick (Little, Brown and Company, 2010)
You are indestructible. These are the words that transfer an astonishing power to Jacob Fielding... and it changes everything. After all, there's something addictive about testing the limits of fear, experiencing the thrill of walking through fire, or saving your friend from a beating in front of the whole school. Then Ophelia James, the beautiful and daring new girl in town, suggests that they use the power to do good, to save others at risk of death. But with every heroic act, the power grows into the specter of a curse. How to decide who lives and who dies? And why does darkness seem to be chasing them? Jacob only has thirteen days to figure out how to harness this terrifying power... and the answer is chilling: "What if he has to kill the one he loves to save her?
Keywords: Adolescence; Adventure; Juvenile Fiction